Carapace scute pattern anomalies in the loggerhead turtle: are they indicative of hatchling's survival probability?. (29th December 2019) - Maffucci, F.; Pace, A.; Affuso, A.; Ciampa, M.; Treglia, G.; Pignalosa, A.; Hochscheid, S.
Abstract: The carapacial scute pattern is a conserved trait in sea turtles that provides taxonomic information, although hatchlings with aberrant scute numbers are commonly described in all extant species. These anomalies have been associated with reduced individual fitness, but very little is known about their occurrence in the juvenile and adult portion of the population. Here, we compared the frequencies of major non‐modal scute patterns (i.e. number of vertebral/coastal scutes ≠ 5, MNMSP) in hatchling, juvenile and adult loggerhead turtles ( Caretta caretta ) from the Central Tyrrhenian Sea. 20.5% of the analysed hatchlings exhibited MNMSP ( N = 1047, range 0–52%). These individuals were significantly lighter than modals, but no other morphological difference was observed. Hatchlings from relocated nests ( N = 241) had a lower rate of scute variation compared to those from natural nests ( N = 806, MNMSP frequencies 10.37 and 23.57% respectively). The proportion of MNMSP decreased in early juveniles (12.1%, N = 149, SCLst < 41 cm) and even further in late juveniles/adults (4.8%, N = 124, SCLst > 41 cm). These results are coherent with those from previous studies and suggest that individuals with modal scute pattern may have a greater survival rate. However, selection against abnormal scute patterns may not occur within the first few days of life, as previously suggested, but it is probably a much slower process that may require several years. It is unlikely that alterations of the scute pattern affect survival directly; they may be a phenotypic expression of underlying morphological or physiological anomalies that stem from environmental stressors similar to those causing scute variations during embryonic development. Abstract : The carapacial scute pattern in the loggerehead turtle is 5 pairs of vertebrals and 5 costals (a), although hatchlings with aberrant scute numbers are commonly described (b, c). Previous studies hypothesised that hatchling turtles with non modal scute numbers have reduced survival chances but little is known about their occurrence in juveniles and adults. Here we analyse a comprehensive data set spanning all age classes of loggerhead turtles to investigate whether the frequency of occurrence of scute anomalies decreases with age, and we were indeed able to confirm this trend (e). Our findings support the hypothesis that abnormal scute patterns are phenotypic expression of underlying morphological or physiological abnormalities that are related to a lower individual survival probability. We also provide new insight on the possible role of temperature and nest relocation during incubation that may have impact on commonly adopted conservation measures on sea turtle nesting beaches.